2014
DOI: 10.1080/17441692.2014.947302
|View full text |Cite
|
Sign up to set email alerts
|

A responsive evaluation of mental health treatment in Cambodia: Intentionally addressing poverty to increase cultural responsiveness in therapy

Abstract: Mental health issues are significant contributors to the global burden of disease with the highest incidence in resource poor countries; 90% of those in need of mental health treatment reside in low resource countries but receive only 10% of the world's resources. Cambodia, the eighth least developed country in the world, serves as one example of the need to address mental health concerns in low-income, resource poor countries. The current study utilises responsive evaluation methodology to explore how poverty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Cambodia continues to rebuild from decades of civil war and the Khmer Rouge genocide. Mental health needs are especially high with regard to anxiety disorders (24.7%) depression (16.7%) and posttraumatic stress disorder (7.6%) (Khann et al, 2016), and are exacerbated by extreme poverty (Seponski et al, 2014). Governmentally, there is a lack of infrastructure, a decentralized mental health system, and limited funding available for mental health services (Stewart, Tsong and Peou, 2010).…”
Section: Mental Health In Cambodiamentioning
confidence: 99%
See 1 more Smart Citation
“…Cambodia continues to rebuild from decades of civil war and the Khmer Rouge genocide. Mental health needs are especially high with regard to anxiety disorders (24.7%) depression (16.7%) and posttraumatic stress disorder (7.6%) (Khann et al, 2016), and are exacerbated by extreme poverty (Seponski et al, 2014). Governmentally, there is a lack of infrastructure, a decentralized mental health system, and limited funding available for mental health services (Stewart, Tsong and Peou, 2010).…”
Section: Mental Health In Cambodiamentioning
confidence: 99%
“…Interest in family therapy is increasing in Cambodia (Seponski, Lewis and Megginson, 2014), yet psychotherapy practice is not sanctioned or licensed and there are no formalized training or supervision requirements (Chan, 2013;Sim, 2012). Due to the newness of therapy training, the availability of supervisors in Cambodia is limited and supervision is conducted by visiting Western or expatriate therapists (Nhong Hema, personal communication, 26 March 2010).…”
mentioning
confidence: 99%
“…The importance of culturally appropriate mental healthcare has also been recognised previously [ 56 59 ], resonating with the third theme, “Developing a model for the Cambodian culture and context.” Mental health service development has to be affordable and appropriate for the current situation in Cambodia. The post-conflict societal context, cultural influences and health beliefs in Cambodia require additional efforts to develop community-based mental health services that are appropriate for the country’s current needs.…”
Section: Discussionmentioning
confidence: 80%
“…The importance of culturally appropriate mental healthcare has also been recognised previously [56][57][58][59], resonating with the third theme, "Developing a model for the Cambodian culture and context. " Mental health service development has to be affordable and appropriate for the current situation in Cambodia.…”
Section: Discussionmentioning
confidence: 98%
“…Testimonial therapy has been previously used in Cambodia and has served as an opportunity for communal and individual healing (Agger, Igreja, Kiehle, & Polatin, 2012). As the model demonstrated that current stressors at individual and community levels were more salient than previous war traumas in impacting PTSD symptoms, such interventions need to be combined with a focus on alleviating poverty and providing more accessible mental and physical health care (Jarl et al, 2015;Seponski, Lewis, & Megginson, 2014).…”
Section: Discussionmentioning
confidence: 99%